Price-making in mineral provisioning systems and social-ecological transformation? The cases of copper, cobalt and lithium - Cornelia Staritz; Bernhard Tröster; Aleksandra Wojewska (Austrian Foundation for Development Research (ÖFSE), 2023)
Research and debates around mineral extraction in the context of social-ecological transformation have dedicated limited focus on price-making processes. Drawing on the systems of provisioning approach, this paper assesses price-making and related institutions in mineral provisioning as contested processes. We argue that price-making is not an objective or solely technical process taking place on abstract markets; rather, it is, first, reflective of power struggles over specific rules and devices between different actors, embedded in social relations, network practices and institutions and, second, linked to characteristics of specific materialities of commodities and territorial and organizational forms of their provisioning. Empirically, we analyze the 'electric vehicle metals' copper, cobalt and lithium, for which derivative markets are intensifying their role as key price-determination institutions linked to financial actors' interest to get price exposure. The paper criticizes current shifts to benchmark- and derivative markets-based price-determination. This approach primarily focuses on short-term and narrow production costs without considering local producer-region specificities, broader economic impacts and environmental and social costs and risks. Moreover, it fails to address the long-term insecurities related to resource depletion. With financial actors dominating price-determination on derivative markets, prices deviate even from such a short-term and narrow fundamental perspective. Alternative price-making mechanisms are needed for social-ecological transformation, which requires political debates and democratic decision-making. Methodologically, the paper is based on trade and financial data and semi-structured interviews with price-determination institutions, metal provisioning and producer country actors.
Keywords: 330; price-making; provisioning systems; infrastructures; financialization; electric vehicle metals